1999
DOI: 10.1200/jco.1999.17.7.2105
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Recombinant Interleukin 2 Therapy for Patients With Metastatic Melanoma: Analysis of 270 Patients Treated Between 1985 and 1993

Abstract: High-dose IL-2 treatment seems to benefit some patients with metastatic melanoma by producing durable CRs or PRs and should be considered for appropriately selected melanoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
1,320
1
20

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,930 publications
(1,388 citation statements)
references
References 29 publications
19
1,320
1
20
Order By: Relevance
“…[13][14][15] Altogether, numerous clinical studies performed during the last decade showed that almost invariably 'cancer vaccines' yielded a modest clinical response rate (as measured by rigorous RECIST criteria) of no more than 5-10%. 16 Strikingly, though, most responses were quite durable 16 and in line with observations from studies using non-specific immune modulators such as recombinant interleukin-2 17 and anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4) monoclonal antibodies. 18,19 Previously, in an attempt to improve on the in vivo generation and amplification of TAA-specific T cells, we clinically evaluated the intra-lymph node administration of two individual plasmids encompassing either MART-1/Melan-A or tyrosinase antigen fragments in stage-III and IV melanoma patients with measurable disease.…”
Section: Introductionsupporting
confidence: 71%
“…[13][14][15] Altogether, numerous clinical studies performed during the last decade showed that almost invariably 'cancer vaccines' yielded a modest clinical response rate (as measured by rigorous RECIST criteria) of no more than 5-10%. 16 Strikingly, though, most responses were quite durable 16 and in line with observations from studies using non-specific immune modulators such as recombinant interleukin-2 17 and anti-cytotoxic T-lymphocyte antigen-4 (CTLA-4) monoclonal antibodies. 18,19 Previously, in an attempt to improve on the in vivo generation and amplification of TAA-specific T cells, we clinically evaluated the intra-lymph node administration of two individual plasmids encompassing either MART-1/Melan-A or tyrosinase antigen fragments in stage-III and IV melanoma patients with measurable disease.…”
Section: Introductionsupporting
confidence: 71%
“…Interpretation of the results was complicated by the fact that 13/14 responders also received high doses of interleukin-2, a drug known to have antitumor effects. 27 Marchand et al 28 observed regression of metastases in 7/25 patients treated with subcutaneous injections of an aqueous solution of a synthetic peptide derived from a protein encoded by the melanomaassociated gene MAGE-3 and presented in the context of HLA-A1. Nestle et al 29 treated 16 metastatic melanoma patients with a novel immunotherapy: autologous dendritic cells pulsed with either synthetic peptides or lysates of autologous melanoma tissue and then injected directly into the regional lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Early single-institutional and multi-institutional single-arm clinical trials of high-dose IL-2 in patients with metastatic melanoma revealed objective response rates of 16-17%, including a 6-7% complete response rate. 42,43 Further followup has shown 80-90% of complete responders remain alive 10-15 years later. 7 Durability and consistency of responses led to the FDA approval of IL-2 for metastatic melanoma in 1998.…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…The mechanism of action for most immunotherapeutic agents remains incompletely understood, but these treatments are notable for their ability to produce a durable benefit in a subset of patients. 7,8 Ipilimumab has been associated with significant improvement in overall survival in the metastatic setting. 5,9 Immunotherapy requires special attention to several caveats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation